Structural validation of the Wong-Law Emotional Intelligence Scale (WLEIS): Preliminary study in adults - Merino Soto, César (2016)
The measurement of emotional intelligence has had many proposals in the form of self-report. One of these is the Wong-Law Emotional Intelligence Scale (WLEIS), created for the job context and which evaluates valuation and the expression of self-emotions; valuation and recognition of emotions in others; regulation of one’s own emotions and the use of emotion to facilitate performance. There is little psychometric evidence regarding the Wong-Law Emotional Intelligence Scale in the Spanish speaking world, which could lead to it also being little used in research and professional practice. The objective of this study is to present the first results of the internal structure validity of the WLEIS in Peruvian adults. There were 120 participants (72 women) between 17 and 59 years old who responded to the questionnaire mediated by the internet. The internal structure was analyzed using structural equations methodology. A satisfactory structure of 4 factors and high factorial loads of items was found. The inter-factorial correlations were high or moderately high – and the internal consistency was good. It is concluded that the first results are acceptable – to assume that the Wong-Law model is also apparently generalizable.